Impact of drug therapy on long-term prognosis in patients with ischemic chronic heart failure with preserved ejection fraction and renal dysfunction - D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
Improvement of the treatment of cardiovascular disease has led to an increase number of patients with chronic heart failure with preserved ejection fraction (HFpEF), but at the moment there is no differentiated approach based on the principles of evidence-based medicine.